Frequency and cause of verb tense error in students’ writing - Yenita Br Sembiring; Reynaldi Kuanda; Parlinggoman Gohae (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2026)
This study examines the frequency and causes of verb tense errors produced by English students of Universitas Prima Indonesia in academic writing. Using a qualitative descriptive approach supported by quantitative data, the study analyzed 60 short essays based on the Surface Strategy Taxonomy framework, which includes omission, addition, misformation, and misordering. A total of 200 tense-related errors were identified and categorized into five tense groups: simple past, simple present, present perfect, future, and continuous forms. The results show that errors in the simple past tense were the most frequent, followed by errors in the simple present and present perfect tenses. Among the error types, misformation errors accounted for the largest proportion, indicating that students struggle with selecting and forming appropriate verb structures. Interview findings further reveal that first language transfer, limited exposure to contextualized grammatical input, overgeneralization of rules, and inadequate proofreading strategies contribute to these errors. Overall, the findings suggest that students’ tense errors are systematic and reflect interlanguage development rather than random mistakes. The study highlights the importance of combining explicit grammar instruction with contextualized writing practice to improve grammatical accuracy in EFL academic writing.